2009
DOI: 10.9775/kvfd.2011.3699
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Grazing and Concentrate Supplementation at Pasture on Performance and Rumen Parameters in Lambs

Abstract: Bu çalışmada, kuzuları merada otlatma ve meraya ilave konsantre yem verilmesinin besi performansı, rumen pH, toplam uçucu yağ asitleri ve amonyak azotu üzerine etkisi araştırılmıştır. Ayrıca, vejetasyon dönemine bağlı olarak meranın besin madde içerikleri de belirlenmiştir. Araştırmada sütten kesilmiş 2-3 aylık yaşta, 18 baş Tuj ırkı erkek kuzu kullanılmıştır. Araştırmada kuzular 6 başlı üç gruba ayrılmıştır. Meraya ilave olarak kuzulara %18.5 HP ve 2.650 kcal/kg ME içeren konsantre yem verilmiştir. Kuzulardan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 7 publications
2
7
0
1
Order By: Relevance
“…The pH, amonnia-N (NH3-N) and total volatile fatty acids (TVFA) contents of rumen liquid which are used to identify in vitro true digestibility of fodders, were found to be as 6.58 (5.91-6.85), 307 mg / l (264-402 mg / l) and 117 mmol / L (88-134 mmol / l), respectively. It was observed that the rumen liquid used in this study complies with the literature reports and that it offers standard rumen liquid properties (Kaya et al 2011;Sahin et al 2013).…”
Section: Forage Quality and The Impact Of Different Forage Types On Ivtdsupporting
confidence: 77%
“…The pH, amonnia-N (NH3-N) and total volatile fatty acids (TVFA) contents of rumen liquid which are used to identify in vitro true digestibility of fodders, were found to be as 6.58 (5.91-6.85), 307 mg / l (264-402 mg / l) and 117 mmol / L (88-134 mmol / l), respectively. It was observed that the rumen liquid used in this study complies with the literature reports and that it offers standard rumen liquid properties (Kaya et al 2011;Sahin et al 2013).…”
Section: Forage Quality and The Impact Of Different Forage Types On Ivtdsupporting
confidence: 77%
“…However, final weight at the end of fattening and DLWG determined in the extensive group of this study were higher compared to values stated by Sarıçiçek et al [14] in Karayaka lambs for final weight (22.34 kg) and DLWG (78.14 g) in the pasture group. The reason for differences between studies was caused from differences in breed, Even though final weight at the end of fattening period stated in this study for semi-intensive group was lower than final weights (44.92 and 46.88 kg) of Tuj lambs in the groups which were given with 200 and 400 g concentrated feed along with pasture in the study conducted by Kaya et al [15] , DLWG was higher than DLWG values (160.57 and 183.14 kg) stated by the same researchers. DLWG in semiintensive group in this study was higher than DLWG values (98 and 118 g) in groups fed additionally in the study conducted by Saatcı et al [16] .…”
Section: Discussionmentioning
confidence: 54%
“…the diets with 15 or 17% crude protein, suggesting that a protein level near 15% would be optimal for 25 to 40 kg growing lambs. In other studies, there was found no effect of protein level on DM intake, daily gain and feed efficiency (Kaya et al, 2009;Rocha et al 2004).…”
Section: Effects Of Different Protein Levels On Fattening Performance...mentioning
confidence: 86%
“…The need for protein depends largely on the breed, body weight and digestibility of protein in feed. In the finishing period, the need for crude protein (CP) level differs from 10-14.7% according to live weight and growing potential (Kaya et al, 2009). In other studies, it is suggested that the optimum CP level required in fattening lamb's diets is usually in the range of 14 to 16% (Milton and Paterson, 2001).…”
Section: Introductionmentioning
confidence: 99%